Correlation of the configuration of the slopes of Yliki and Paralimni (Viotia) with the tectonics. - Papadopoulou-Vrynioti, K; Vassilopoulos, A.; Evelpidou, N. (Water in 21st century: Problems-Prospects Conference, 2003)
In this paper the area of Iliki and Paralimni karstic lakes is studied through fieldwork and GIS. The study area is situated east of the Fokida – Beotia tectonic depression focusing on the relation of the tectonic activity to the formation of the surrounding slopes. As a result of this study, slope formation is related to the two main tectonic phases of the wider area.